UJI AKTIVITAS ANTIOKSIDAN EKSTRAK BAWANG PUTIH (Allium sativum) - Djuned Prasonto; Eriska Riyanti; Meirina Gartika (Odonto : Dental Journal, 2017)
Background: Organosulfur compound, allicin and phenolic are the main compound in garlic responsible for antioxidant activity. Correlation between free radicals and some dental diseases, such as free radicals and Reactive Oxygen Species (ROS) responsible for periodontal inﬂammation, caries, lesions and oral cancers. The research objective is to get scientifc data about the antioxidant activity from garlic extract (Allium sativum).Method: The research was conducted using three diﬀerent varieties of garlic:local garlic varieties Ciwidey, single local garlic’s clove, and import garlic which is found at the market in Bandung. Garlic extract is made by maceration using ethanol 96% and antioxidant activity test using DPPH method (1,1-diphenyl-2- picrylhydrazyl). Statistical analysis using One Way ANOVA followed by post hoc analysisResult: three varieties of garlic have a strong antioxidant activity. Value of IC50 = 13.61 mg / ml for local garlic varieties Ciwidey, IC50 = 10.61 mg/ml for single local garlic’s clove and IC50 = 11.32 mg/ml for imports garlic.Conclusion: Three varieties of garlic have diﬀerent antioxidant strength and the best antioxidant strength is single local garlic’s clove.